Multigene-locus cpDNA Bayesian frameworks in resolving conflicts within Philippine endemic Gardenia Ellis (Rubiaceae) Implications to taxonomy, biodiversity and drug development - Chavez, Jayson G. (Transactions of the National Academy of Science and Technology, 2011)
The Philippine Gardenia specie form a highly heterogeneous assemblage, leading to several taxonomic transfers to other Rubiaceous genera (Ceriscoides, Discospermum, Fagerlindia, Sulitia, Vidalasia, and Villaria). Inspite of these taxonomic rearrangements, three remaining Philippine endemic Gardenia species (G. lagunensis Merr., G merrillii Elmer and G. negrosensis Merr.) still exhibit disparate features against the current circumscription of the genus and remain unsolved. In order to evaluate their true generic affinities with more certitude, we conducted separate and combined Bayesian Inference (BI) of the rps16 intron and trnT-F region sequences of cpDNA. The majority rule consensus tree of the combined dataset is more congruent with the rps16 intron tree but with much higher Posterior Probabilities (PP). The four sampled Philippine Gardenia species including G. elata appeared into two different group in the tribe Gardenieae. Gardenia elata grouped within the Gardenia clade with high support (PP=1.00), while G. lagunenis, G. merrillii, and G. negronensis nested within a clade with Rothmannia annae and R. capensis with strong support (PP=0.96). These molecular findings are congruent with morphology such as the 3:3 nodal pattern of leaves, absence of domatia, bilobed stigmas, 2-locular ovaries, globular indehiscent fruits and seeds that are embedded in a pulp forming a single mass. Therefore, we recognized three novel combinations under Rothmannia Thunb., which established for the first time the genus to the archipelago. In relation to this taxonomic breakthrough, implications on their conservation status and possible medicinal use are presented.